Perceived Adequate Office Facilities and Academic Staff Job Performance in Federal Colleges of Education in Northwest Zone, Nigeria - Tukur , Muhammad; Ammani, Abubakar (Kashere Journal of Education, 2025)
This research investigated the adequacy of office facilities and the performance of academic staff in the Northwest zone of Nigeria's federal colleges of education. The study employed a correlational research design. The population of the study was 2,211 lecturers, of which 322 were sampled using proportionate and simple random sampling techniques. The data collection instruments titled ‘Lecturers’ Questionnaire for the Adequacy of Office Facilities' and 'Lecturers' Performance Questionnaire' (LQAOFLPQ) were adapted for the study and validation was done by three experts drawn from the faculty of education and extension services, Usmanu Danfodiyo University, Sokoto. The research questions were answered using descriptive statistics (mean and standard deviation) and the hypothesis was tested using the Pearson Product Moment Correlation Coefficient at the 0.05 significance level. The study found out that the office facilities in the colleges were fairly adequate. The study also found out a significant positive correlation (r = 0.513, p < 0.05) between the adequacy of office facilities and academic staff job performance. The study concluded that the additional office facilities improvement will result in enhanced teaching, research, and academic services. The study recommended, among others that Federal Government through the National Commission for Colleges of Education and allied agencies, needs to provide more additional office facilities for academic staff in federal colleges of education in the Northwest Zone, Nigeria, especially ICT gadgets.